Integrating islamic spirituality in teacher training: Analysis of Faculty Development Programs and their impact on teaching practices - Azme , Nasibah (Journal of Islamic, Social, Economics and Development, 2024)
The significance of integrating Islamic spirituality-based pedagogy into teacher training programs for the enhancement of both academic and moral teaching is now widely recognized. This paper attempts to analyze the role of Islamic spirituality as a component in teacher training programs by looking at several faculty developments models. Additionally, this paper explores the types of teacher training programs in integrate spirituality at the respective faculty. Rather than providing instruction in institutional policy and regulations, as is the case in professional programs, these programs focus on spiritual leadership, ethical teaching, and reflective practice to educate educators who are academically proficient as well as capable of moral and spiritual development of their students. This paper explains that integrating Islamic spirituality within educator training improves teaching methodology, fostering student engagement, and enables holistic education. Although the benefits are clear, there are significant challenges, particularly in secular educational settings where balancing religious teachings with secular rules requires careful negotiation. This paper examines these challenges, including the shortage of trained Islamic educators and the difficulties of integrating religious values within secular systems. Nevertheless, positive ways of providing an opportunity are via inter-religious dialogue and can build a mutual understanding among the different nationalities in multicultural classrooms. Moreover, it is imperative to fill these gaps and complete training programs that involve tackling both religious and secular goals with a view to making Islamic spirituality successfully embedded in education.